On-line examination system of security application - Paleti, Tarun; Kumar, Kiran; Riyaz, Shaik (International Journal of Engineering and Technology, 2018)
Online Examination Framework is Associate in Nursing programming arrangement, That which allows any Education system or institution to orchestrate, direct and superintend exams by suggests that of an internet domain. It may be done through the Web/Intranet and/Neighborhood System things. a little of the problems confronted amid manual examination frameworks ar the postponements occured in result handling, documenting represents a difficulty, separating of records is difficult . the chance of loss of records is high in addition record seeking is difficult . repairs of the framework is in addition exceptionally difficultand takes parcel of your time and labour. on-line examination is one in all the vital elements for on-line instruction framework. it’s effective, sufficiently fast and reduces the intensive live of fabric plus. Associate in Nursing examination framework is formed in light-weight of the net. This paper depicts the quality of the framework, displays the basic parts of the framework, breaks down the auto-producing check paper calculation, and talks concerning the protection of the framework.